Bilateral renal lymphoma: rapid recovery from an acute kidney injury after open renal biopsy. Issue 1 (7th October 2015) - Mitome, Taku; Furuya, Kazuhiro; Imano, Masashi; Osaka, Kimito; Yokomizo, Yumiko; Hayashi, Narihiko; Nakaigawa, Noboru; Yamanaka, Shoji; Yao, Masahiro
Key Clinical Message: Renal lymphoma as an initial lesion is relatively rare. Bilateral renal lymphoma frequently presents as acute kidney injury. With systematic chemotherapy for the lymphoma, patients usually recover their kidney function. However, in the case we describe here, the patient's kidney function recovered greatly after an open renal biopsy. Here, we review and discuss this unique case. Abstract : Renal lymphoma as an initial lesion is relatively rare. Bilateral renal lymphoma frequently presents as acute kidney injury. With systematic chemotherapy for the lymphoma, patients usually recover their kidney function. However, in the case we describe here, the patient's kidney function recovered greatly after an open renal biopsy. Here, we review and discuss this unique case.